1986
DOI: 10.1525/aa.1986.88.3.02a00030
|View full text |Cite
|
Sign up to set email alerts
|

Human Emotions: Universal or Culture‐Specific?

Abstract: The search for “fundamental human emotions” has been seriously impeded by the absence of a culture‐independent semantic metalanguage. The author proposes a metalanguage based on a postulated set of universal semantic primitives, and shows how language‐specific meanings of emotion terms can be captured and how rigorous cross‐cultural comparisons of emotion terms can be achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
100
0
16

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 220 publications
(116 citation statements)
references
References 13 publications
0
100
0
16
Order By: Relevance
“…They, however, documented the similarity, not difference, in the structure of the emotion lexicons between English, Hindi, and a host of other languages and cultures. Of course, the articles by Russell (1991) and Wierzbicka (1986) mentioned above are also germane here as well.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They, however, documented the similarity, not difference, in the structure of the emotion lexicons between English, Hindi, and a host of other languages and cultures. Of course, the articles by Russell (1991) and Wierzbicka (1986) mentioned above are also germane here as well.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship between culture and language for emotion, in fact, has received considerable attention in both the psychological and anthropological literatures, and most likely contributes to cultural differences in emotion judgment (e.g., see reviews by Russell, 1991, andWierzbicka, 1986).'' The fact that we were not able to backtranslate disgust and contempt accurately leads us to suspect that some of the same underlying phenomena that produced the cultural differences in emotion recognition accuracy may have contributed to our difficulty in finding adequate translations of these words.…”
Section: Discussionmentioning
confidence: 99%
“…Brain stimulation studies, which have identified the neurobiological systems eliciting these emotions (namely the PLAY system, the RAGE system, the FEAR system, the DISGUST system and the PANIC system; see Panksepp, 1998Panksepp, , 2006Toronchuk & Ellis, 2007a, 2007b, provide strong evidence that at least some discrete emotions are not culture specific (Ekman & Friesen, 1971;Wierzbicka, 1986), but are found universally, even in different mammalian species. Thus, it is believed that the DENN-BAWL would not only allow investigations with German-speaking participants, but may also trigger broader, cross-cultural comparisons, given that norms are available in two languages, and given the likely universal neurobiological basis of the discrete emotion effects.…”
Section: Introductionmentioning
confidence: 99%
“…Wierzbicka (1986) has pointed out the difficulty ofobtaining exact translation equivalents in a domain where there are no clear Munsell chip-like equivalences to match them against. She argues that it may be best to attempt to define words according to universal semantic primitives instead, although how this might be done in the absence ofa theoretical approach to the domain is not at all clear (see Russell, 1991, p. 442).…”
Section: Discussionmentioning
confidence: 99%